When Veps Cry: Two-Year-Olds Efficiently Learn Novel Words from Linguistic Contexts Alone. Issue 1 (2nd January 2018) - Ferguson, Brock; Graf, Eileen; Waxman, Sandra R.
ABSTRACT: We assessed 24-month-old infants' lexical processing efficiency for both novel and familiar words. Prior work documented that 19-month-olds successfully identify referents of familiar words (e.g., The dog is so little) as well as novel words whose meanings were informed only by the surrounding sentence (e.g., The vep is crying), but that the speed with which they identify the referents of novel words lagged far behind that for familiar words. Here we take a developmental approach, extending this work to 24-month-olds. By comparing the performance of 19- and 24-month-olds directly, we document that during this period of rapid vocabulary growth, infants make significant processing gains for both familiar and novel words. We also offer the first evidence to date that, at both 19- and 24-months, the number of verbs infants know predicts their ability to use known verbs to learn novel nouns. These results reveal that 24-month-olds can efficiently learn novel words just by listening to the conversations around them.